Opinion formation on complex social networks: a simulation study - Sun, Xingyue (Nanyang Technological University, 2022)
Nowadays, people are inundated with all kinds of information every day, everyone is a social sensor that detects and experiences information. The mode of social network opinion formation is an important aspect of public opinion research, and also an important content of current social management. This dissertation establishes an opinion formation model for the feature of social network information credibility based on the classic Deffuant-Weisbuch model and introduces an opinion leader node to simulate the role of an opinion leader in the process of opinion formation. The experimental results show that the convergence speed of opinions is positively correlated with the initial objective credibility of information, which affects the overall judgment of the masses on the situation. Opinion leader has a guiding role. Individuals in social networks are influenced by opinion leaders, and their opinions will continue to move closer to the opinion leaders. The research has certain significance for people to deeply understand the internal mechanism of the formation and evolution of opinions, provides new ideas to further study the evolution of public opinions, and has important theoretical value for guiding and controlling the spread of public opinions.